Novel Outphasing Power Amplifiers Designed With an Analytic Generalized Doherty-Chireix Continuum Theory - Liang, Chenyu; Roblin, Patrick; Hahn, Yunsik; Popovic, Zoya; Chang, Hsiu-Chen (IEEE transactions on circuits and systems. I, Regular papers, 2019)
An analytic theory for dual-input outphasing power amplifiers that incorporate in one unified treatment, the continuum of solutions for power combining including the Doherty and Chireix modes is presented. This unified theory developed at the current-source reference planes reveals the performance trade-off achieved by all of the possible power amplifier (PA) combiners within the continuum of solutions. Furthermore, it identifies a novel type of dual-input hybrid Chireix-Doherty PA that combines key features of the Doherty and Chireix operations such that the fundamental drain voltages applied to both the main and auxiliary transistors remain constant. This hybrid PA relies on an input outphasing angle varying with the input power level to obtain the correct load modulation behavior. A 2-GHz dual-input hybrid Chireix-Doherty PA is implemented using nonlinear embedding and experimentally evaluated to validate the theory. A drain efficiency of 61% at 9-dB backoff power and a maximum output power of about 43 dBm are obtained for continuous-wave (CW) measurements. The efficiency increases monotonously with output power unlike that of the Doherty PA used for comparison. When excited with a 20-MHz LTE signal with 9.5-dB peak-to-average power ratio (PAPR), the dual-input PA yields a 60.0% average drain efficiency and −48.1-dBc adjacent-channel power-leakage ratio (ACLR) after linearization.